2012
DOI: 10.1186/1471-2369-13-116
|View full text |Cite
|
Sign up to set email alerts
|

Mineral and bone disorder in Chinese dialysis patients: a multicenter study

Abstract: BackgroundMineral and bone disorder (MBD) in patients with chronic kidney disease is associated with increased morbidity and mortality. Studies regarding the status of MBD treatment in developing countries, especially in Chinese dialysis patients are extremely limited.MethodsA cross-sectional study of 1711 haemodialysis (HD) patients and 363 peritoneal dialysis (PD) patients were enrolled. Parameters related to MBD, including serum phosphorus (P), calcium (Ca), intact parathyroid hormone (iPTH) were analyzed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 21 publications
5
36
1
Order By: Relevance
“…Our study revealed that total serum ALP levels were associated with higher all-cause and cardiovascular mortality in PD patients, independent of serum calcium, phosphorus, iPTH, and liver enzymes (AST and ALT). It was reported that bone mineral disease characteristics are different in PD and HD (9) and that bone microarchitecture is more severely affected in patients on HD than patients receiving PD (8); however, our study indicated that the association between ALP and mortality in PD patients is similar with the previous study in HD patients (6).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Our study revealed that total serum ALP levels were associated with higher all-cause and cardiovascular mortality in PD patients, independent of serum calcium, phosphorus, iPTH, and liver enzymes (AST and ALT). It was reported that bone mineral disease characteristics are different in PD and HD (9) and that bone microarchitecture is more severely affected in patients on HD than patients receiving PD (8); however, our study indicated that the association between ALP and mortality in PD patients is similar with the previous study in HD patients (6).…”
Section: Discussionsupporting
confidence: 51%
“…Additionally, a cross-sectional study in China found that mineral and bone disorder (MBD) in PD patients is not as serious as in HD patients (9). However, whether a similar association between ALP and mortality also exists in PD patients is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Impaired renal phosphate clearance results in phosphate accumulation in the serum, which cannot be corrected by dialysis alone. Hence, >50% of patients undergoing hemodialysis (HD) or peritoneal dialysis (PD) show elevated serum phosphate concentrations above the level recommended in the current guidelines [1,2]. Hyperphosphatemia is an independent predictor for cardiovascular and all-cause mortality in patients undergoing dialysis, because it contributes to vascular calcification, ventricular hypertrophy, additional mineral dysmetabolism, etc.…”
Section: Introductionmentioning
confidence: 99%
“…It is most prevalent among CKD patients receiving dialysis, with published estimates of prevalence ranging from 47 to 80 % [1][2][3][4]. A recent report from the COSMOS study found that most hemodialysis patients (70.5 %) had serum phosphorus levels that were above the normal range recommended by the kidney disease: improving global outcomes (KDIGO) guidelines (3.0-4.5 mg/dL) [4].…”
Section: Introductionmentioning
confidence: 99%